2018
DOI: 10.18280/mmc_a.910105
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour based navigational control of humanoid robot using genetic algorithm technique in cluttered environment

Abstract: Humanoids are popular than their wheeled counterparts by the virtue of their ability to mimic the human behaviour and replace human efforts if required. Navigation and path planning is a complex and challenging problem for humanoids as it involves careful consideration of the navigational parameters. This paper introduces the path planning of a humanoid robot utilizing genetic hereditary calculation. The objective of the paper is to design a navigational controller using genetic algorithm for path planning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…They used the sensor information like obstacle distances and location of target as input to the controller and obtained streaming angle as output from the controller. Rath et al 6 presented genetic algorithm-based controller for path planning of a humanoid in complex environments with static and dynamic hurdles. They developed an objective function for path optimization and performed in both simulation and experimental platform.…”
Section: Introductionmentioning
confidence: 99%
“…They used the sensor information like obstacle distances and location of target as input to the controller and obtained streaming angle as output from the controller. Rath et al 6 presented genetic algorithm-based controller for path planning of a humanoid in complex environments with static and dynamic hurdles. They developed an objective function for path optimization and performed in both simulation and experimental platform.…”
Section: Introductionmentioning
confidence: 99%
“…Lamini et al (2018) have conducted a study for resolving the difficulties encountered in path planning and suggested an improved crossover operator for the method of genetic algorithm. Rath et al (2018b) have implemented the genetic heredity calculation in the path planning of a humanoid robot. The main aim of the investigation was to make a prototype of a navigation controller implementing the genetic algorithm for the course with obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Navigational analysis of mobile robotic forms using various soft computing methods (Mohanty & Parhi, ; Mohanty & Parhi, ; Pandey & Parhi, ; Parhi, Deepak, Mohana, Ruppa, & Nayak, ; Parhi & Kundu, ) have been attempted by several researchers. Rath et al (Rath, Das, Parhi, & Kumar, ; Rath, Parhi, Das, & Kumar, ; Rath, Parhi, Das, Muni, & Kumar, ) have discussed possible uses of nature inspired algorithms in humanoid navigation.…”
Section: Introductionmentioning
confidence: 99%